2010
DOI: 10.1111/j.1550-7408.2010.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐Tubulin and Small Subunit rRNA Phylogenies of Peritrichs Are Congruent and Do Not Support the Clustering of Mobilids and Sessilids (Ciliophora, Oligohymenophorea)

Abstract: ABSTRACT. Peritrich ciliates have been traditionally subdivided into two orders, Sessilida and Mobilida within the subclass Peritrichia. However, all the existing small subunit (SSU) rRNA phylogenetic trees showed that the sessilids and mobilids did not branch together. To shed some light on this disagreement, we tested whether or not the classic Peritrichia is a monophyletic group by assessing the reliability of the SSU rRNA phylogeny in terms of congruency with a-tubulin phylogeny. For this purpose, we obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 28 publications
3
31
0
Order By: Relevance
“…Previous alpha-tubulin phylogenies showed that most classes could be well distinguished with high support [8], [15], [20], while subclasses appeared to be non-monophyletic [13], [21], [29]. In our recent study [13], we characterized alpha-tubulin gene from 15 genera covering all families of the order Urostylida, but we were unable to determine if alpha-tubulin gene is suitable for classification of lower level taxa since urostylid families are not well defined morphologically [31], [32] and their monophyly is rejected by both SSU-rDNA and alpha-tubulin phylogenies.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous alpha-tubulin phylogenies showed that most classes could be well distinguished with high support [8], [15], [20], while subclasses appeared to be non-monophyletic [13], [21], [29]. In our recent study [13], we characterized alpha-tubulin gene from 15 genera covering all families of the order Urostylida, but we were unable to determine if alpha-tubulin gene is suitable for classification of lower level taxa since urostylid families are not well defined morphologically [31], [32] and their monophyly is rejected by both SSU-rDNA and alpha-tubulin phylogenies.…”
Section: Introductionmentioning
confidence: 94%
“…However, protein-coding genes can possess paralogs that might bias phylogenetic trees [27], [28]. Among these protein-coding genes, alpha-tubulin is one of the mostly used gene makers for ciliated phylogeny [8], [11], [13], [15], [20], [21], [29], and its duplication in ciliates has been previously studied only with sparse taxon sampling [15], [30]. Therefore, alpha-tubulin is a promising candidate for testing whether protein-coding genes are suitable for phylogeny construction of ciliates.…”
Section: Introductionmentioning
confidence: 99%
“…Shazib et al (2014) included sequences of 28S-rDNA and ITS in phylogenetic reconstructions of Heterotrichea, but because they used a reduced number of taxa, the obtained topologies showed low resolution, and deeper nodes of the heterotrichean tree remained undefined. It is generally assumed that the region of internal spacers of ribosomal small subunit ITSI-5.8S-ITSII and the cytochrome oxidase subunit I (COI) are reliable molecular markers for inferring Ciliophora phylogeny, although phylogenies inferred using these markers differed from those obtained with 18S-rDNA (Gong et al, 2010;Sun et al, 2010;Yi and Song, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…At the time, it was suggested that the taxon sampling might be inadequate. Even with increased taxon sampling, investigations have failed to unite the two lineages (Gong et al, 2006(Gong et al, , 2010Li et al, 2008;Utz and Eizirik, 2007;Utz et al, 2010). Even so, the monophyly of the Peritrichia could not be rejected when employing statistical tests (Utz and Eizirik, 2007).…”
Section: Introductionmentioning
confidence: 99%